2018
DOI: 10.1007/s11626-018-0284-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-uc.40 silence promotes P19 embryonic cells differentiation to cardiomyocyte via the PBX1 gene

Abstract: Uc.40 is a long noncoding RNA that is highly conserved among different species, although its function is unknown. It is highly expressed in abnormal human embryonic heart. We previously reported that overexpression of uc.40 promoted apoptosis and inhibited proliferation of P19 cells, and downregulated PBX1, which was identified as a potential target gene of uc.40. The current study evaluated the effects of uc40-siRNA-44 (siRNA against uc.40) on the differentiation, proliferation, apoptosis, and mitochondrial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, based on GO and KEGG pathway analyses, we found that target genes of highly differentially expressed lncRNAs were mainly involved in pathways including regulation of actin cytoskeleton, actin dynamics signaling pathway, and so on. Among the 9 target genes of hsa-miR-4505, CRAT [26,27], ITGB5 [19,28,29], SMIM5 [30], CHI3L1 [31], GPC6 [32,33] and PBX1 [34] have been con rmed as the key target genes for cardiac function damage in hemodialysis patients. In addition, functional prediction of the target genes revealed that ITGB5 was enriched in actin dynamics signaling pathway, which was consistent with the results of functional enrichment analysis of related lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, based on GO and KEGG pathway analyses, we found that target genes of highly differentially expressed lncRNAs were mainly involved in pathways including regulation of actin cytoskeleton, actin dynamics signaling pathway, and so on. Among the 9 target genes of hsa-miR-4505, CRAT [26,27], ITGB5 [19,28,29], SMIM5 [30], CHI3L1 [31], GPC6 [32,33] and PBX1 [34] have been con rmed as the key target genes for cardiac function damage in hemodialysis patients. In addition, functional prediction of the target genes revealed that ITGB5 was enriched in actin dynamics signaling pathway, which was consistent with the results of functional enrichment analysis of related lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of uc40-siRNA44 increases the number of cardiac stem cells during P19 cell differentiation. It promotes the proliferation of P19 cells and inhibits apoptosis induced by serum starvation, which may play a role in regulating PBX1 60 .…”
Section: Pbx1 Structure Development and Function In Regenerative Medi...mentioning
confidence: 99%
“…In this mechanism, Mef2c is negatively regulated by uc.167, however, overexpression of Mef2c can reverse the effects of uc.167 [ 10 ]. Uc.40 also has a known role in inhibiting the proliferation and differentiation of cardiomyocytes by downregulating Pre-B-cell leukemia homeobox transcription factor 1 (PBX1) expression [ 11 ]. Interestingly, although uc.245 has no direct effects on the cell cycle, it can play the same role as the ucRNAs discussed above by downregulating the expression of friend of GATA 2 (FOG2).…”
Section: Physiologymentioning
confidence: 99%